Лучшие помощники
- Megamozg 2205 б
- Matalya1 1800 б
- DevAdmin 1720 б
- arkasha_bortnikov 895 б
- Dwayne_Johnson 860 б
To solve for x in the equation log7(x^2-12x+36)=0, we need to use the definition of logarithms which states that log(base a) b = c is equivalent to a^c = b.
In this case, we have log7(x^2-12x+36)=0, which means that 7^0 = x^2-12x+36.
Simplifying 7^0, we get 1, so x^2-12x+36 = 1.
Rearranging the equation, we get x^2-12x+35 = 0.
We can factor this equation as (x-5)(x-7) = 0.
Therefore, the solutions are x = 5 and x = 7.
Checking these solutions, we can see that log7(1) = 0, so both x = 5 and x = 7 satisfy the original equation.
In this case, we have log7(x^2-12x+36)=0, which means that 7^0 = x^2-12x+36.
Simplifying 7^0, we get 1, so x^2-12x+36 = 1.
Rearranging the equation, we get x^2-12x+35 = 0.
We can factor this equation as (x-5)(x-7) = 0.
Therefore, the solutions are x = 5 and x = 7.
Checking these solutions, we can see that log7(1) = 0, so both x = 5 and x = 7 satisfy the original equation.
0
·
Хороший ответ
31 марта 2023 17:18
Остались вопросы?
Еще вопросы по категории Математика
Что означает число 1 4 в десятичной системе счисления?...
Как перевести 100 километров в метры?...
Do you have to pay for parking at this mall?...
Какой оператор используется в выражении '1 3 плюс 1 6'?...
в основании прямой призмы находится равнобедренный треугольник со сторонами 10;13 и 13 см. Найдите объем призмы если длина её бокового ребра равн...